An assessment of the Clean Development Mechanism (CDM) potential in Pakistan’s Industrial sugar sector - Rabiya Nasir; Abdullah Yasar; Sabiha Javied; Rab Nawaz; Sajjad Ahmad; Laila Shahzad (Kuwait Journal of Science)
Sugar product is an important industry in Pakistan and contributes 1.9% to the GDP. However, the sugar industry is emitting a number of gaseous pollutants through inefficient burning of bagasse and polluting the environment with the release of high wastewater amount. To mitigate this problem in such industries, the Clean Development Mechanism (CDM) is introduced by which highly renewable energy efficient technologies are employed. This study was conducted to find out the potential of the CDM in the industrial sugar sector of Pakistan. Two models of bagasse and biogas utilization in sugar industry were used to estimate electricity generation and carbon reduction. The results show that the sugar industry of Pakistan had the potential of 2,033MW of electricity production and 232,5968t CO2 eq of Certified Emission Reduction (CER) annually. Certification processes were the major barriers in the implementation of the CDM in the sugar industry.